The Use of Antibody-Antibiotic Conjugates to Fight Bacterial Infections - Cavaco, Marco; Castanho, Miguel A. R. B.; Neves, Vera (Frontiers in Microbiology, 2022)
The emergence of antimicrobial resistance (AMR) is rapidly increasing and it is one of the significant twenty-first century's healthcare challenges. Unfortunately, the development of effective antimicrobial agents is a much slower and complex process compared to the spread of AMR. Consequently, the current options in the treatment of AMR are limited. One of the main alternatives to conventional antibiotics is the use of antibody-antibiotic conjugates (AACs). These innovative bioengineered agents take advantage of the selectivity, favorable pharmacokinetic (PK), and safety of antibodies, allowing the administration of more potent antibiotics with less off-target effects. Although AACs' development is challenging due to the complexity of the three components, namely, the antibody, the antibiotic, and the linker, some successful examples are currently under clinical studies.